ASSESSING THE PRACTICALITY OF REWARD SYSTEMS: THE CASE OF THE "HAPPY AND SAD LIST" - Demmy Tabuni; Paskalis Kaipman; Ivona Dorobia (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT The implementation of reward systems in classrooms has been widely adopted to encourage positive behavior and enhance students' learning motivation. However, studies examining the psychological and pedagogical implications of openly grouping students through the happy and sad list approach remain limited. This study aimed to analyze the implementation of a reward system using the happy and sad list approach by examining its implications for students' behavior, learning motivation, and psychological development. The study employed a qualitative case study design using an authentic case published in The Psychologist as the unit of analysis. Data were analyzed through repeated reading, thematic coding, and interpretive analysis using theoretical triangulation by integrating perspectives from behaviorism, incentive theory, labeling theory, and the humanistic approach. The findings indicate that this approach can promote positive behavior, increase classroom participation, and strengthen learning motivation when implemented fairly and supported by positive reinforcement. Conversely, inappropriate implementation may lead to negative labeling, reduced self-efficacy, emotional discomfort, and diminished learning motivation. These findings underscore the importance of balancing positive reinforcement, students' psychological well-being, equitable instructional practices, and collaboration between schools and families to foster an inclusive learning environment. ABSTRAK Penerapan reward system di kelas telah banyak digunakan untuk mendorong perilaku positif dan meningkatkan motivasi belajar peserta didik. Namun, kajian mengenai implikasi psikologis dan pedagogis dari pengelompokan peserta didik secara terbuka melalui pendekatan happy and sad list masih terbatas. Penelitian ini bertujuan menganalisis penerapan reward system melalui pendekatan happy and sad list dengan mengkaji implikasinya terhadap perilaku, motivasi belajar, dan perkembangan psikologis peserta didik. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus yang memanfaatkan kasus autentik yang dipublikasikan dalam The Psychologist sebagai unit analisis. Data dianalisis melalui pembacaan berulang, pengodean tematik, dan interpretasi menggunakan triangulasi teori yang mengintegrasikan perspektif behaviourism, incentive theory, labelling theory, dan pendekatan humanistik. Hasil penelitian menunjukkan bahwa pendekatan tersebut dapat mendorong perilaku positif, meningkatkan partisipasi kelas, dan memperkuat motivasi belajar apabila diterapkan secara adil serta didukung positive reinforcement. Sebaliknya, penerapan yang tidak tepat berpotensi menimbulkan pelabelan negatif, menurunkan self-efficacy, memicu ketidaknyamanan emosional, dan mengurangi motivasi belajar. Temuan ini menegaskan pentingnya pengelolaan perilaku yang menyeimbangkan penguatan positif, kesejahteraan psikologis, praktik pembelajaran yang adil, serta kolaborasi sekolah dan keluarga dalam membangun lingkungan belajar yang inklusif.